Probing and Tuning the Permeability of Polymersomes - Miller, Alisha J. (ACS Cent Sci, 2020)
[Image: see text] Polymersomes are a class of synthetic vesicles composed of a polymer membrane surrounding an aqueous inner cavity. In addition to their overall size, the thickness and composition of polymersome membranes determine the range of potential applications in which they can be employed. While synthetic polymer chemists have made great strides in controlling polymersome membrane parameters, measurement of their permeability to various analytes including gases, ions, organic molecules, and macromolecules remains a significant challenge. In this Outlook, we compare the general methods that have been developed to quantify polymersome membrane permeability, focusing in particular on their capability to accurately measure analyte flux. In addition, we briefly highlight strategies to control membrane permeability. Based on these learnings, we propose a set of criteria for designing future methods of quantifying membrane permeability such that the passage of a variety of molecules into and out of their lumens can be better understood.